The Role of Capital Market Literacy in Mediating the Effect of Social Media and Financial Motivation on the Behavior of Young Investors in Indonesia - Afrizal Zaki, Anas; Tubastuvi, Naelati (Journal of Accounting and Finance Management, 2025)
This study aims to examine the influence of social media and financial motivation on the investment behavior of young investors, with capital market literacy serving as a mediating variable. The research targets young investors aged 18–30 years who are actively engaged in the Indonesian capital market. Employing a quantitative approach, the study collected data through a survey of 218 young investors and analyzed the data using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 3. The findings reveal that both social media and financial motivation have a positive and significant effect on capital market literacy. Social media also exerts positive influence on investor behavior, while financial motivation does not have a direct effect on investor behavior. Capital market literacy demonstrates the most substantial impact on young investors’ behavior and significantly mediates the relationship between social media and financial motivation with investment behavior. These results underscore the critical role of capital market literacy in transforming information and motivation into rational investment actions. This study provides both theoretical and practical contributions toward fostering a more intelligent and sustainable investment ecosystem among Indonesia’s young generation.